Palm Pre : the missing manual. - Baig, Edward C. (Missing manual., 2009)
If you've got your hands on this year's hottest new smartphone, you'll want the book that covers it inside and out: Palm Pre: The Missing Manual . This beautiful, full-color book from USA Today personal-technology columnist Ed Baig will help you go from newcomer to expert in no time. The maker of the legendary Palm Pilot is back on center stage with a smartphone that lets you browse the Web, listen to music, watch video, view pictures, and a lot more. Palm Pre: The Missing Manual provides you with everything you need to know to get the most out of this amazing mobile tool. Get to know the touchscreen, and learn to navigate by tapping, swiping, dragging, flicking, and pinching Link your contacts, merge calendars, combine email accounts, and more by syncing your phone over the Web Stay in touch with other people by using the Pre as a full-featured phone and organizer Use it for email, texting, chatting, and as an efficient web browser Take advantage of the Pre as a complete media center to store, sort, play, stream music and video, and sync with iTunes Take and view photos, import images, and share them with others.